Polysplenia Syndrome, Heterotaxy with Jejunal Atresia: A Case Report - Mazen O. Kurdi; Abdel-Rahman R. Abdel-Halim (Journal of King Abdulaziz University: Medical Sciences, 2023)
Heterotaxy is defined as an abnormality where the internal thoracoabdominal organs show abnormal arrangements across the left-right axis of the body. It might affect the stomach alone, i.e. dextrogastria. This anomaly can be combination of dextrogastria with functional asplenia (asplenic or hyposplenic) and other visceral heterotaxy with possible malrotation. Heterotaxy is rare condition and its association with intestinal atresia is almost very rarely reported in the literature. Presented is a case of heterotaxy with dextrogastria, multiple small splenules and associated with Type 2 jejunal atresia with brief review of the literature.